Direct Amination of Phenols under Metal-Free Conditions - Yu, Jianzhong; Wang, Yongtao; Zhang, Peizhi; Wu, Jun (Synlett, 2013)
Herein, we disclose the metal-free synthesis of arylamines via the direct amination of phenols using aminating reagents. This reaction procedure uses easy accessible aminating reagents and provides a versatile synthetic route to a broad range of arylamines with various functionalities in good to excellent yield. By using a two-step route of amination and oxidative coupling reaction, we synthesized three naturally occurring carbazole alkaloids: murrayafoline A, mukonine, and clausenine from two commercially available phenols.
Keywords: amination; phenols; metal-free; arylamines; carbazoles